N‐acylhomoserine lactone‐regulation of genes mediating motility and pathogenicity in Pseudomonas syringae pathovar tabaci 11528 - Cheng, Feifei (Microbiologyopen, 2017)
Pseudomonas syringae pathovar tabaci 11528 (P. syringae 11528) is a phytopathogen that causes wild‐fire disease in soybean and tobacco plants. It utilizes a cell density‐dependent regulation system known as quorum sensing (QS). In its QS system, the psyI is responsible for the biosynthesis of N‐acylhomoserine lactones (AHLs). By comparing the transcripts from P. syringae 11528 wild‐type strain with those of the ΔpsyI mutant using RNA sequencing (RNA‐seq) technology, 1118 AHL‐regulated genes were identified in the transition from exponential to stationary growth phase. Numerous AHL‐regulated genes involved in pathogenicity were negatively controlled, including genes linked to flagella, chemotaxis, pilus, extracellular polysaccharides, secretion systems, and two‐component system. Moreover, gene ontology and pathway enrichment analysis revealed that the most pronounced regulation was associated with bacterial motility. Finally, phenotypic assays showed that QS‐regulated traits were involved in epiphytic growth of pathogens and disease development in plants. These findings imply that the AHL‐mediated QS system in P. syringae 11528 plays significant roles in distinct stages of interactions between plants and pathogens, including early plant colonization and late plant infection.